Evolution through genetic exchange - Arnold, Michael L. (Michael Lynn) (Oxford : Oxford University Press, 2006)
This is the first book to focus on the rapidly expanding field of reticulate (non-treelike) or network evolution. Written by a top researcher in the field, this book includes a wealth of examples from viral, prokaryotic and eukaryotic clades.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Evolutionary genetics; Hybridization